Mucor tofus, a new species isolated from Mao-tofu (a fermented soybean food) in China - Wang, Ya-Ning; Zheng, Ru-Yong (Phytotaxa, 2022)
During studies on the diversity of Mucorales associated with traditional fermentation food from China, two Mucor strains were isolated from the surface of Mao-tofu, a fermented soybean food. Phylogenetic analyses of the internal transcribed spacer (ITS) and the large subunit (LSU) rDNA sequences revealed that the new isolates belong to the M. mucedo group and are closely related to M. mucedo. However, they differ from other species of this group by producing swollen, tall sporangiophores, sporangia measuring 40–260 µm and irregular sporangiospores. The maximum growth temperature of the new isolates is 33 °C, which is higher than other species in the M. mucedo group. Based on the combination of morphological characteristics, growth experiments and molecular phylogenetics, a new species Mucor tofus is proposed. Detailed phylogenetic trees, descriptions and illustrations are provided.